IMPLICATIONS OF BIOMATERIALS AND MODERN TECHNOLOGIES IN FIXED PROSTHETIC REHABILITATION OF PATIENTS WITH DIFFERENT SYSTEMIC DISEASES - Cristina Iordache; Irina Gradinaru; Irina Eșanu; Ana Maria Fătu; Alina Apostu; Bogdan Vascu; Cristina Gena Dascalu; Codrina Ancuța; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2023)
The therapeutic solutions chosen were ceramics on a zirconium support or ceramics on a metal infrastructure made by laser technique, which is a therapeutic alternative beneficial for the relationship with the affected tissues, a situation that is found in patients with cardiovascular or other types of general diseases. In addition to the technological line chosen, the biomaterials chosen are also extremely important, with Co-Cr alloys remaining a biocompatible option that satisfies the optimal parameters of the final prosthetic construction. From the study group we selected a representative clinical case for cardiovascular pathology in conjunction with partial edentulousness.The aim of this study is to identify how modern fixed prosthodontic technologies optimize the integration of fixed prostheses in the context of the current oral manifestations which occur as a consequence of different types of systemic damage.The study group consisted of 200 patients diagnosed with different forms of partial edentulousness and at the same time presenting different general status disorders. Non-invasiveness in conjunction with precise modern technologies with a different degree of biocompatibility creates the prerequisites for a good integration of oral rehabilitation against the background of different types of complications in the territory of oral manifestations in patients with different types of systemic diseases.